Serological cross-reactivity of Trypanosoma cruzi, Ehrlichia canis, Toxoplasma gondii, Neospora caninum and Babesia canis to Leishmania infantum chagasi tests in dogs - Zanette, Maurício Franco; Lima, Valéria Marçal Felix de [UNESP]; Laurenti, Márcia Dalastra; Rossi, Claudio Nazaretian; Vides, Juliana Peloi; Vieira, Rafael Felipe Da Costa; Biondo, Alexander Welker; Marcondes, Mary [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2014)
Introduction: The aim of this study was to evaluate the serological cross-reactivity between Leishmania sp. and other canine pathogens. Methods: Positive serum samples for Ehrlichia canis, Babesia canis, Toxoplasma gondii, Neospora caninum and Trypanosoma cruzi were tested using three serological methods enzyme linked immunosorbent assay (ELISA), indirect immunofluorescent antibody test (IFAT) and Kalazar Detect™, for canine visceral leishmaniasis. Results: Of the 57 dog samples tested, 24 (42.1%) tested positive using one of the three serological methods: 10/57 (17.5%) for ELISA, 11/57 (19.3%) for IFAT and 3/57 (5.3%) for Kalazar Detect™. Conclusions: Our results demonstrated that the presence of other infectious agents may lead to cross-reactivity on leishmaniasis serological tests.
Keywords: Diagnosis; Serology; Visceral leishmaniasis